Gnpat does not play an essential role in systemic iron homeostasis in murine model. Issue 7 (28th February 2020) - An, Peng; Wang, Jiaming; Wang, Hao; Jiang, Li; Wang, Jia; Min, Junxia; Wang, Fudi
Abstract: The GNPAT variant rs11558492 (p.D519G) was identified as a novel genetic factor that modifies the iron‐overload phenotype in homozygous carriers of the HFE p.C282Y variant. However, the reported effects of the GNPAT p.D519G variant vary among study populations. Here, we investigated the role of GNPAT in iron metabolism using Gnpat ‐knockout ( Gnpat −/− ), Gnpat / Hfe double‐knockout ( Gnpat −/− Hfe −/− or DKO) mice and hepatocyte‐specific Gnpat ‐knockout mice ( Gnpat fl/fl ;Alb‐Cre ). Our analysis revealed no significant difference between wild‐type ( Gnpat +/+ ) and Gnpat −/− mice, between Hfe −/− and DKO mice, or between Gnpat fl/fl and Gnpat fl/fl ;Alb‐Cre with respect to serum iron and tissue iron. In addition, the expression of hepcidin was not affected by deleting Gnpat expression in the presence or absence of Hfe. Feeding Gnpat −/− and DKO mice a high‐iron diet had no effect on tissue iron levels compared with wild‐type and Hfe −/− mice, respectively. Gnpat knockdown in primary hepatocytes from wild‐type or Hfe −/− mice did not alter hepcidin expression, but it repressed BMP6‐induced hepcidin expression. Taken together, these results support the hypothesis that deleting Gnpat expression has no effect on either systemic iron metabolism or the iron‐overload phenotype that develops in Hfe −/− mice, suggesting that GNPAT does not directly mediate iron homeostasis under normal or high‐iron dietary conditions.